Blai Guarné, ed. 2018. Antropología de Japón. Identidad, discurso y representación. Barcelona: Bellaterra. 312 pp. - de Vargas, Ferran (Estudios de Asia y África, 2021)
Blai Guarné, ed. 2018. Antropología de Japón. Identidad, discurso y representación. Barcelona: Bellaterra. 312 pp.